Bleeding During Veno-Venous ECMO: Prevention and Treatment - Kalbhenn, Johannes; Zieger, Barbara (Frontiers in Medicine, 2022)
Venovenous extracorporeal membrane oxygenation (vvECMO) has become a routine treatment for severe lung failure in specialized centers. Spontaneous bleeding complications, however, are observed in 30%-60% of patients during vvECMO treatment. Bleeding increases mortality by factor 2-3. Anticoagulation in combination with several acquired bleeding disorders caused by the mechanical pump and the foreign layer of the extracorporeal system contribute to the risk of bleeding. In this review mechanisms of the underlaying pathologies and the route from diagnosis to treatment are described.